Exploring Practices and Teacher Voices on the Use of Engoo in Online Speaking Classrooms - Assakhi, Sanna Mohammad; Suci, Dewi Nur; Melynia, Frisca Juniar (Proceeding International Conference on Education, 2024)
Incorporating digital media into education has shifted how language is learned. This study aims to explore how Engoo can potentially be utilized in EFL learning to teach speaking skills and find out teachers’ voices on its perceived usefulness in an online context. Observations in online learning classrooms and interviews with the five teachers in two English course institutions were conducted to collect the data. The results of this study show that Engoo serves as an effective platform for teaching EFL speaking skills that consists of information in the forms of written text, pictures, and audio. This platform can be a resourceful material to teach speaking for the students across level. Additionally, the majority of the teachers had positive impressions and experiences towards the use of Engoo for their EFL instructions. As a result, future research can expose the students’ voices in using Engoo and the effectiveness of that online learning media.